Introduced or established? Convergent evidence indicates imported pine wood nematode vectors occupy gaps in native distribution - Jean-Claude Grégoire; Jean Artois; Julien Claude; Marius Gilbert; Serge Morand; Géraldine Roux; Gilles San Martin; Dimitrios Avtzis; Nick Berkvens; Jochem Bonte; Hans Casteels; Sandra Closa; et al. (Journal of Pest Science, 2026)
Monitoring regulated quarantine plant pathogens and, when relevant, their vectors is compulsory in the European Union. Local Monochamus species (Coleoptera, Cerambycidae) vector the pine wood nematode, Bursaphelenchus xylophilus , a non-native pest already established in most of Portugal. Only 29 M. galloprovincialis individuals were trapped in Belgium in ten years (2013–2022), despite a dense coverage of pheromone-baited traps, suggesting absence or a very rare local occurrence in the country. In the northern neighbouring countries, only one single established population is known in The Netherlands and one in Denmark. A species distribution model based on pheromone-trap catches (negative and positive) of M. galloprovincialis from 4,914 traps in 29 European countries between 2008 and 2019 was developed, using the overall climate conditions and the distribution of seven pine tree species as explanatory variables. The effect of spatial scale was tested with a multi-scale approach. With a 225*225 km spatial grain, the major explanatory variables were the mean diurnal temperature range and, to a lesser extent, the presence of Pinus spp. The model predicted a low probability of presence in Belgium, the Netherlands, Great Britain and north-western Germany compared to southern Europe. Genotyping allowed to conclude that at least some of the beetles caught in Belgium originated from foreign locations. All catches were located close to entry points, suggesting introduction with imported material. The small size of most of the Belgian pine stands may also explain the absence or apparently transient status, or rareness of Monochamus spp. This study thus suggests that surveys in Belgium should privilege entry points rather than local forest stands.